AKSESIBILITAS UNTUK PENGUNJUNG DIFABEL DI OBYEK WISATA MUSEUM BENTENG VREDEBURG - , Haritsah Kusumaningrum, Prof. Dr. Ir. Chafid Fandeli, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The concern about accessible tourism has grown, and nowadays accessibility has become one of the main focuses in tourism. This development in accessible tourism was driven by the needs to give people with disability equal service and experience of tourism. The main goal of this research is to identify those needs for people with disability. Taking Benteng Vredeburg Museum as a case study, this research is trying to uncover whether the Benteng Vredeburg Museum in narrow scope (and Indonesian tourism in general) has addressed those needs or not. This research is also trying to find what the considerations are when the Museum is making a policy regarding accessibility for people with disability. In order to achieve those two goals described above, a descriptive-qualitative research method is being use in this research. This method is considered as an appropriate and effective tool to achieve the goals of this research. The data for this research is mainly being gathered using in-depth interview with the subject of this research, which are: the people with disability, the accompanying person, and the museum representatives. After the data was gathered, in a descriptive-qualitative research, these following steps were carried out: data reduction (filtering), data description, and hypothesis making. After all of those steps was finished, these following research facts were surfacing. Firstly, the needs of visitor with visual impairment are guiding blocks, tactile map, sign, lightning, audio, Braille text, and hands on. Furthermore the needs of visitor with mobility impairment are accessibility in parking area, ramps, doors, toilet, pathways, sign, plenty of seats, enough space in exhibit room, and displays are in suitable height. Secondly, the building infrastructure of Benteng Vredeburg Museum is barely accessible for people with disability. This Museum was not designed for an easy access for people with disability. Furthermore, the exhibits in this museum were also not designed for people with disability. Those exhibits are basically designed only for able bodied people. Thirdly, the Museum has recently revitalized their accessibility policy to address the increasing demand for an accessible tourism. But those changes were not able to provide the needs for all types of disability.